Dampak Manajemen SDM Perpustakaan dalam Menunjang Optimalisasi Kegiatan Akademik Mahasiswa di IAIN Kediri - Nurwarniatun (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
This research was conducted in order to determine the role of the Librarian in the process of optimizing performance and also to find out the quality and quality provided in library service at IAIN Kediri, East Java. This type of research is conducted using qualitative research. This research uses observation and interview techniques with the resource persons, the librarian who is also the head of the IAIN Kediri library. In this study, the results are obtained regarding the fact that good management and management of a librarian in providing library services is very important and gives a very big influence on the satisfaction of users and the achievement of the goals of a library. Like a librarian who must always be friendly and provide the best service and always be innovative in managing library materials in the library. Thus the suggestion for the head of the library is to 1) always provide quality and accurate library materials, 2) the user as a source of information must be able to maximize the use of available resources in order to provide the best and optimal service performance.